Imprensa negra e ensino de História: o debate sobre a questão racial em São Paulo na Primeira República - Tavares, Francilene De Souza [UNIFESP] (2021)
This thesis has as perspective that the press is an historical and political agent who search to highlight how the journals produced by and for the black people reported racism, prejudice and racial discrimination which men and women have suffered in the beginning of twentieth century in São Paulo. Through the analysis of journals as A Liberdade - órgão crítico, literário e noticioso, dedicado à classe de cor and O Clarim da Alvorada - órgão literário, científico e político it was possible think about the life experiences of these population in São Paulo, once that this journals were like a collective voice of the black population on behalf of the citizenship guarantee and the search of the realization of their rights. Finally, considering the characteristics of ProfHistória program we search to show the pedagogical possibilities to use the black press in classroom highlighting that the usage of these historical sources in classroom can help to reframe the history-identity knowledge from a afro-centered perspective.